Interrogating the Legal/Illegal Frame: Trump Administration Immigration Policy and the Christian Response - Shadle, Matthew Allen (Journal of ecumenical studies, 2020)
Statements on immigration by the United States Conference of Catholic Bishops, the National Council of Churches, and the latter's member communions all counter a simplistic moral distinction between those who immigrate to the United States legally and those who come illegally by addressing the social and economic factors spurring migration, identifying the flaws in the U.S. immigration system, and calling for solidarity between citizens and immigrants, regardless of legal status. The immigration and refugee policies of the Trump administration, however, reveal that the rhetorical distinction between "legal" and "illegal" has less to do with the law than it does with the arbitrary exercise of power and reinforcing racial hierarchies. The churches must learn to address this darker side of anti-immigrant rhetoric more adequately.